Mass Cytometry Study on Hepatic Fibrosis and Its Drug-Induced Recovery Using Mouse Peripheral Blood Mononuclear Cells - Bae, Jiwon; Kim, Ji Eun; Perumalsamy, Haribalan; Park, Sehee; Kim, Yun; Jun, Dae Won; Yoon, Tae Hyun (Frontiers in Immunology, 2022)
The number of patients with liver diseases has increased significantly with the progress of global industrialization. Hepatic fibrosis, one of the most common liver diseases diagnosed in many developed countries, occurs in response to chronic liver injury and is primarily driven by the development of inflammation. Earlier immunological studies have been focused on the importance of the innate immune response in the pathophysiology of steatohepatitis and fibrosis, but recently, it has been also reported that adaptive immunity, particularly B cells, plays an essential role in hepatic inflammation and fibrosis. However, despite recent data showing the importance of adaptive immunity, relatively little is known about the role of B cells in the pathogenesis of steatohepatitis fibrosis. In this study, a single cell-based, high dimensional mass cytometric investigation of the peripheral blood mononuclear cells collected from mice belonging to three groups (normal chow (NC), thioacetamide (TAA), and 11beta-HSD inhibitor Drug) was conducted to further understand the pathogenesis of liver fibrosis through reliable noninvasive biomarkers. Firstly, major immune cell types and their population changes were qualitatively analyzed using UMAP dimensionality reduction and two-dimensional visualization technique combined with a conventional manual gating strategy. The population of B cells displayed a two-fold increase in the TAA group compared to that in the NC group, which was recovered slightly after treatment with the 11beta-HSD inhibitor drug. In contrast, the populations of NK cells, effector CD4+ T cells, and memory CD8+ T cells were significantly reduced in the TAA group compared with those in the NC group. Further identification and quantification of the major immune cell types and their subsets were conducted based on automated clustering approaches (PhenoGraph PG) and FlowSOM). The B cell subset corresponding to PhenoGraph cluster PG#2 (CD62L+CD44+Ly6c+ B cells) and PG#3 (CD62L+CD44+Ly6c- B cell) appears to play a major role in both the development of hepatic fibrosis and recovery via treatment. Whereas, PG#1 (CD62L- CD44+Ly6c- B cell) seems to play a dominant role in the development of hepatic fibrosis. These findings provide insights into the roles of cellular subsets of B cells during the progression of, and recovery from, hepatic fibrosis.